Mengukur Kinerja Keuangan PT. Semen Gresik, Tbk Menggunakan Metode Leverage Analysis - Maulana, Wahyu; Marsum, Marsum (Universitas Gajah Putih, 2021)
The purpose of this study is to measure the financial performance of the company which in this case is a cement industry company listed on the BEI using leverage analysis. The data collected is in the form of financial reports published from 2017 to 2019. This type of research is quantitative research using secondary data sources. The data analysis technique is in the form of a leverage ratio formula. The results show that the results of calculations and data analysis for the Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER) and Long Term Debt to Equity Ratio (LDER) fluctuate, while the Times Interest Earned Ratio (TIER) has increased every year. This company's financial performance for DAR and TIER is solvable (good) while for DER and LDER it is insolvable (bad) so it is the company's duty to improve performance in these indicators and maintain good performance going forward.